An Adaptive Photovoltaic Performance Study with a Biomimetic Approach for Energy Saving - Kevin Ananda; Agus Hariyadi (Universitas Atma Jaya Yogyakarta, 2023)
The facade has a function to improve the energy performance of the building by controlling the acquisition of sunlight and natural lighting. The biomimetic architecture approach is one form of architecture that imitates the principles of nature—integrating photovoltaics with facades to utilize solar lighting and generate electricity for building needs. The novelty of this study aims to examine the effectiveness of adaptive facade forms with a biomimetic approach integrated with photovoltaic on heat transfer and energy saving and determine the factors that influence it. This study uses the parametric modeling simulation method. In addition, this study compares aspects of heat transfer and energy generated by photovoltaics on adaptive facades with a biomimetic approach. The study's results using a flower petal-shaped adaptive biomimetic facade showed that OTTV 35 watt/m2 (standard) obtained all grid configurations with an opening angle of 10-20 degrees, and the average electrical energy produced by integrated Photovoltaic was around 1,757.7 kWh. This result provides energy savings of 20.03% on a building.